The deregulated physiology in oral squamous cell carcinoma- a brief review - Keerthika Saravanan; Madhu Narayan; Krishnan Rajkumar (Oral Oncology Reports)
Cancer is a major health burden globally. Not only the disease but also its treatment ravages a patient afflicted with it. Decoding its pathogenesis in entirety and the process through which it is able to not only survive but also grow indefinitely despite the inherent immune mechanisms of the human body is an area of continuous research. In cancer biology, hallmarks of cancer represent the normal physiology gone astray such as sustaining proliferative signaling, evading growth suppressors, avoiding immune destruction, activating invasion and metastasis, tumor promoting inflammation, enabling replicative immortality, inducing angiogenesis and resisting cell death that thus serve as blueprints for understanding core cancer characteristics. The main aim of this review is to get a general understanding of the mechanisms in which the physiology gets deregulated in oral squamous cell carcinoma and to highlight its importance in producing an effective treatment through targeting them. To write this review article, databases like PubMed, Embase, Cochrane and Google Scholar were searched and those articles relating to the hallmarks of cancer published in English between 1993 and 2023 were considered. The applicable data was extracted from the related articles and included in a single review.